Vaginal douching by women with vulvovaginitis and relation to reproductive health hazards - Shaaban, Omar M (BioMed Central, 2013)
BACKGROUND: Vaginal douching (VD) is a common practice among married women all over the world specially those in the Middle East. It is used for personal hygiene or for other aesthetic reasons in many countries. The current study investigates the prevalence of VD among patients with vulvovaginitis in Egypt. It also compares the reproductive health hazards among women performing routine VD with those using external hygiene. It also investigates why, and how women practice this douching. METHODS: A cross sectional observational study was conducted in a tertiary university affiliated hospital in Assiut, Egypt. An interview administered questionnaire was administered to 620 women by two trained clinic nurses. Women presented to the outpatient clinic and diagnosed to have any type of vaginal infections were approached for participation. The principle outcome was the history of preterm labor in women who routinely performed VD versus those who did not (upon which sample size was estimated). Other outcome measures were the types of vaginal infections, and reproductive implications comprising, ectopic pregnancy, abortion and pelvic inflammatory disease (PID). RESULTS: The participants were predominantly multiparas from semi-urban background and middle socioeconomic level. Considering VD as a religious duty and a kind of personal cleanliness were the most common reasons for performing VD in 88.9% and 80.6% of the studied population, respectively. History of preterm labor was reported in 19.2% versus 11.9% (p=0.048), while history of PID in 13.2% versus 6.0% (p=0.008) in women performing VD compared to those not performing this habit, respectively. There were no significant differences between the two groups as regard the history of ectopic pregnancy or the number of previous abortions. CONCLUSION: Vaginal douching is a prevalent practice in Egypt and has traditional and religious roots within the community. There are many misbeliefs around this habit in Egypt. Vaginal douching increases certain reproductive health hazards especially preterm labor and PID. Much effort and awareness campaigns are needed to increase women awareness about health hazards of this incorrect practice and to limit its use.